(untitled) (Research, Society and Development, 2020)
The study aimed to identify the sedentary habits and nutritional status of a futsal school under 12-13 from a municipality located in the interior of Ceará. This is a descriptive, quantitative and cross-sectional study, which participated 22 athletes from a sub 12-13 futsal school belonging to the 1st Stage Project. A questionnaire was used for data collection, and the statistical software SPSS, version 22.0, was used for analyses of the data collected. The results show that the variables that include screen time, have a higher average among the sedentary time variables, with a prevalence higher than 2 hours per day, while on the nutritional status was found the "low or no" consumption of vegetables and fruits. On the other hand, a “low or no” consumption of sugary drinks and chips was identified. In addition, half of the participants make use of buses, cars or motorbikes, which characterize locomotion mechanisms that leave them in physical inactivity.